Popular Culture to Teach Spanish as a Foreign Language (2019)
This paper presents various aspects of a research on teaching Spanish as a foreign language (ELE, by its acronym in Spanish). The project focused on the use of Colombian popular culture to teach Spanish to a group of foreigners at Universidad Pedagógica y Tec- nológica de Colombia, using different narrative and popular texts: the myth, the legend, the proverb and the omen. The purpose of this project was to design and apply a primer, which included some narrative texts with exercises and activities. In relation to the methodology, the research ́s focus was qualitative, insofar as both the collection and analysis of informa- tion and the units ́ design took into account the information provided by the piloting, which allowed the conception of the didactic proposal. As a result, the book Teaching Spanish for foreigners through popular culture was produced, which compiles twelve units that were developed entirely by foreign students. It was concluded that the use of narrative texts (the myth, the legend, the proverb and the omen) allowed the learners to improve their levels of comprehension and expression while expanding their knowledge of Colombian culture